Search for single production of vector-like quarks decaying into a b quark and a W boson in proton–proton collisions at s = 13 TeV - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; Frühwirth, R.; et al. (Elsevier, 2017)
A search is presented for a heavy vector-like quark, decaying into a b quark and a W boson, which is produced singly in association with a light flavor quark and a b quark. The analysis is performed using a data sample of proton–proton collisions at a center-of-mass energy of s=13TeV collected at the LHC in 2015. The data set used in the analysis corresponds to an integrated luminosity of 2.3fb−1. The search is carried out using events containing one electron or muon, at least one b-tagged jet with large transverse momentum, at least one jet in the forward region of the detector, and missing transverse momentum. No excess over the standard model prediction is observed. Upper limits are placed on the production cross section of heavy exotic quarks: a T quark with a charge of 2/3, and a Y quark with a charge of −4/3. For Y quarks with coupling of 0.5 and B(Y→bW)=100%, the observed (expected) lower mass limits are 1.40 (1.0)TeV. This is the most stringent limit to date on the single production of the Y vector-like quark.